Gracilaria gracilis and Nannochloropsis oceanica, singly or in combination, in diets alter the intestinal microbiota of European seabass (Dicentrarchus labrax) - Ferreira, Mariana; Abdelhafiz, Yousri; Abreu, Helena; Silva, Joana; Valente, Luisa M. P.; Kiron, Viswanath (Frontiers in Marine Science, 2022)
Algae feeds and fish gut microbiota have been given importance in the past few years because of the necessity to rely on sustainable ingredients in aquafeeds and the link of host-associated microbes to organismal health. But little is known about the potential of algae, particularly of micro- and macroalgae combination, to shape the intestinal bacterial communities. Hence, in the present work, the 16S rRNA gene sequencing was employed to unravel the effects of the seaweed Gracilaria gracilis and the microalga Nannochloropsis oceanica - included either singly or in combination in the diets of European seabass - on the diversities and composition of the gut bacterial communities. Results indicated that 8% inclusion of either G. gracilis (GRA) or N. oceanica (NAN) led to a reduction in the gut microbial diversity. On the other hand, inclusion of the micro- and macroalga in a blend (NANGRA) mitigated these plausible effects on the intestinal bacterial communities. The core microbiota of European seabass was composed of both beneficial (Lactobacillus and Cetobacterium) and potentially pathogenic (Flavobacterium) bacteria. The GRA diet was associated with a lower abundance of carbohydrate degraders, while also promoting the growth of bacteria capable of outcompeting fish pathogens (Sulfitobacter and Methylobacterium); while the NAN diet led to a higher representation of the genus Bacillus, with probiotic potential, accompanied by a decrease in Vibrio, a genus encompassing several fish pathogenic species. These findings demonstrate the ability of micro- and macroalgae to modulate the gut microbiota of European seabass, with plausible implications to host gut homeostasis.